2006
DOI: 10.1124/dmd.106.010652
|View full text |Cite
|
Sign up to set email alerts
|

Recirculatory Pharmacokinetic Model of the Uptake, Distribution, and Bioavailability of Prochlorperazine Administered as a Thermally Generated Aerosol in a Single Breath to Dogs

Abstract: ABSTRACT:A thermal aerosol generation process is capable of delivering pure drug reliably to the alveoli where it is absorbed systemically. Although deep lung absorption of drugs administered as an aerosol has been shown to be rapid, detailed characterization of their absorption and distribution has not been reported. The present study describes the pharmacokinetics of prochlorperazine from the moment of administration as either a rapid intravenous infusion or a thermally generated aerosol and determines the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…These data are consistent with clinical and preclinical PK analyses of several different drug substances delivered via the Staccato ® system. These studies have generated consistent results, with peak plasma levels observed 3–5 minutes after inhalation, regardless of the drug substance administered (Alexza Pharmaceuticals 2014c; Avram et al 2007; Avram et al 2009; Avram et al 2013; Macleod et al 2012; Rabinowitz et al 2004; Rabinowitz et al 2006; Spyker et al 2010). Another limitation of the present study is the relatively small sample size (N=14).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These data are consistent with clinical and preclinical PK analyses of several different drug substances delivered via the Staccato ® system. These studies have generated consistent results, with peak plasma levels observed 3–5 minutes after inhalation, regardless of the drug substance administered (Alexza Pharmaceuticals 2014c; Avram et al 2007; Avram et al 2009; Avram et al 2013; Macleod et al 2012; Rabinowitz et al 2004; Rabinowitz et al 2006; Spyker et al 2010). Another limitation of the present study is the relatively small sample size (N=14).…”
Section: Discussionmentioning
confidence: 55%
“…By rapidly heating the metal substrate, the drug film is rapidly vaporized to form a highly pure aerosol. The Staccato ® system has previously been shown to deliver drugs with intravenous-like pharmacokinetics in humans and canines, including a rapid onset of pharmacodynamic effects (Avram et al 2007; Avram et al 2009; Avram et al 2013; Rabinowitz et al 2004; Rabinowitz et al 2006). For example, 1 mg of inhaled alprazolam produced peak plasma levels in 3.84 minutes (Alexza Pharmaceuticals 2014a b).…”
Section: Introductionmentioning
confidence: 99%
“…Highly sensitive and selective methods without time-consuming sample pretreatment are desired for bioavailability and bioequivalence studies. The latest assays using LC/MS/MS were reported [8][9][10]. However, due to the low sensitivity (LLOQ of 2.00 ng/ml) [8], long retention time (near 5 min) [9], lacking chromatography and validation details [10], or requirement of special testing equipment (tandem mass spectrometry), those methods were not suitable in most laboratories for studies involving low oral dose for current formulations and samples in high-throughput.…”
Section: Introductionmentioning
confidence: 98%
“…ICG andantipyrine have been used as markers of the vascular space and total body water, respectively. This model is based on catenary compartmental models linked in series [27][28][29][30].…”
Section: Basic Pharmacokinetic Concepts and Some Clinical Applicationsmentioning
confidence: 99%